Multiphase flow modelling in moderately rotating inclined porous media. (5th August 2016) - Härting, Hans‐Ulrich; Lange, Rüdiger; Schubert, Markus
ABSTRACT: Advective and diffusive multiphase flows through vertical porous media are well examined and discussed in the scientific literature. However, uncommon configurations with inclined porous media are examined to a lesser extent, while advanced configurations with superimposed motion have hitherto scarcely been addressed. An example of such configuration is the inclined rotating tubular fixed bed reactor, which is a novel intensified multiphase reactor for heterogeneous catalytic gas‐liquid‐solid reactions (H.‐U. Härting, R. Lange, F. Larachi, M. Schubert, Chem. Eng. J .2015, 281, 931). For the prediction of liquid saturation and two‐phase pressure drop in inclined and moderately rotating confined porous media, a two‐fluid model is presented. The model is one‐directional, isothermal, and considers incompressible Newtonian fluids. To account for the interphase momentum transfer, adopted Ergun‐type closures are formulated taking the peculiarities of stratified, dispersed, and annular flow into account. The effects of inclination and rotation are incorporated as additional body forces, whereby inclination is taken into account by the longitudinal gravity component and a semi‐empirical closure for the complex effects of the rotational velocity is presented. The applicability of the model is validated against experimental liquid saturation and two‐phase pressure drop data.